The Role of Maternal HIV Envelope-Specific Antibodies and Mother-to-Child Transmission Risk - Douglas, Ayooluwa O.; Martinez, David R.; Permar, Sallie R. (Frontiers in Immunology, 2017)
Despite the wide availability of antiretroviral (ART) prophylaxis during pregnancy, >150,000 infants become infected through mother to child transmission (MTCT) of HIV worldwide. It is likely that additional intervention strategies, such as a maternal HIV vaccine, will be required to eliminate pediatric HIV infections. A deeper understanding of the fine-specificity and function of maternal HIV Env-specific responses that provide partial protection against MTCT will be critical to inform the design of immunologic strategies to curb the pediatric HIV epidemic. Recent studies have underlined a role of maternal HIV Env-specific neutralizing and non-neutralizing responses in reducing risk of MTCT of HIV and in prolonging survival rates in HIV-infected infants. However, critical gaps in our knowledge include A) the specific role of maternal autologous-virus IgG neutralizing responses in driving the selection of infant Transmitted Founder (T/F) viruses, and B) Env mechanisms of escape from maternal autologous virus neutralizing antibodies. A more refined understanding of the fine-specificities of maternal autologous-virus neutralizing antibodies and ways that maternal circulating viruses escape from these antibodies will be crucial to inform maternal vaccination strategies that can block MTCT to help achieve an HIV-free generation.